A Tale of Minorities: Evidence on Religious Ethics and Entrepreneurship from Swiss Census Data - Luca Nunziata; Lorenzo Rocco (Institute for the Study of Labor (IZA), 2014)
Does Protestantism favour the market economy more than Catholicism does? We provide a novel quasi-experimental way to answer this question by comparing Protestant and Catholic minorities using Swiss census data from 1970 to 2000. Exploiting the strong adhesion of religious minorities to their confession's ethical principles and the historical determination of the geographical distribution of confessions across Swiss cantons, we find that Protestantism is associated with a significantly higher propensity for entrepreneurship. The estimated difference ranges between 2.3 and 4.4 percentage points. Our findings are robust to a number of robustness checks, including a placebo test.
Keywords: Z12; J24; J21; Z13; 330; entrepreneurship; self-employment; religion; culture; Protestantism; Catholicism; Switzerland